Nigeria Development Update, June 2021 : Resilience through Reforms - World Bank (World Bank, Washington, DC, 2021)
In 2020, Nigeria experienced its deepest recession in four decades, but growth resumed in the fourth quarter as pandemic restrictions were eased, oil prices recovered, and the authorities implemented policies to counter the economic shock. As a result, in 2020 the Nigerian economy experienced a smaller contraction (-1.8 percent) than had been projected when the pandemic began (-3.2 percent). As part of its response, the government carried out several long-delayed policy reforms, often against vocal opposition. Notably, the government (1) began to harmonize exchange rates; (2) began to eliminate gasoline subsidies; (3) started adjusting electricity tariffs to more cost-reflective levels; (4) cut nonessential spending and redirected resources to COVID-19 (coronavirus) responses at both the federal and the state levels; and (5) enhanced debt management and increased public-sector transparency, especially for oil and gas operations. By creating additional fiscal space and maximizing the impact of the government’s limited resources, these measures were critical in protecting the economy against a much deeper recession and in laying the foundation for earlier recovery. However, several critical reforms are as yet incomplete, which threatens Nigeria’s nascent recovery. In the baseline scenario, Nigeria’s economy is expected to grow by 1.8 percent in 2021. Despite the current favorable external environment, with oil prices recovering and growth in advanced economies, reform slippages would hinder the renewed economic expansion and undermine progress toward Nigeria’s development goals. In a risk scenario, in which the government fails to sustain recent macroeconomic and structural reforms, the pace of economic recovery would slow, and GDP growth couldbe just 1.1 percent in 2021.